Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

Traditional plant use in the National Park of Cilento and Vallo di Diano, Campania, Southern, Italy. - Di Novella, Riccardo; Di Novella, Nicola; De Martino, Laura; Mancini, Emilia; De Feo, Vincenzo (Journal of ethnopharmacology, 2012)
AIM OF STUDY: This paper reports an ethobotanical survey of the traditional uses of medicinal and useful plants in an area of the National Park of Cilento and Vallo di Diano, Campania, Southern Italy. MATERIALS AND METHODS: This study conducted between 2009 and 2011, gathered information on the medicinal plants traditionally used in Southern Italy (Campania Region). In all, we interviewed 70 key informants, whose age ranged between 50 and 85 years. This people belonged to families which had strong links with traditional activities of the area. RESULTS: The research resulted to the identification of 192 plants belonging to 64 families. Among the species reported, 86 are used in human medicine, 15 in veterinary medicine, 69 as human foods, 18 as animal feed, 61 for domestic and 8 for agricultural uses. CONCLUSION: A survey of the available literature on Southern Italy ethnobotany reveals that some species have been never reported and about 10% of cited uses are new. Data obtained show that in the studied area the folk use of plants is alive and still derives from daily practice.
The following values have no corresponding Zotero field: publisher: Elsevier accession-num: 23159473
Keywords: Agriculture; Agriculture: methods; Animal Feed; Animal Feed: utilization; Data Collection; Ethnobotany; Ethnobotany: methods; Ethnobotany: statistics & numerical data; Ethnomedicine; Food; Humans; Italy; Medicinal; Medicine; National Park of Cilento and Vallo di Diano; plant traditional uses; Plants; Traditional; Traditional: utilization; Veterinary medicine; Veterinary Medicine: methods

Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Medicinal plants in the Mediterranean area: synthesis of the results of the project Rubia. - González-Tejero, M R; Casares-Porcel, M; Sánchez-Rojas, C P; Ramiro-Gutiérrez, J M; Molero-Mesa, J; Pieroni, A; Giusti, M E; Censorii, E; de Pasquale, C; Della, a; Paraskeva-Hadijchambi, D; Hadjichambis, a; et al. (Journal of ethnopharmacology, 2008)
Within the scope of the European project RUBIA (ICA3-2002-10023), research has been performed on the traditional use and handling of plant species in several Mediterranean countries, Albania, Algeria, Cyprus, Egypt, Italy, Morocco, and Spain. This paper synthesises the chief results related to the medicinal utilization of those plants.
Keywords: Ethnobotany; Medicinal; Medicinal plants; Mediterranean; Mediterranean Region; Plants; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Folk phytotherapeutical plants from Maratea area (Basilicata, Italy). - Guarrera, Paolo Maria; Salerno, Giovanni; Caneva, Giulia (Journal of ethnopharmacology, 2005)
Field ethnobotanical survey was undertaken for the period of 2002-2003 in the Tyrrhenian part of the Basilicata region of southern Italy. Data of 56 species of plants belonging to 29 families where gathered through interviews; among the species, 47 are used in human therapy, 6 as insect repellents, 15 in veterinary medicine, 1 for its ichthyotoxic properties and 3 for magic therapeutic purposes. The most important findings in ethnomedicine relate to Nasturtium officinale (renal colic, liver diseases), Foeniculum vulgare subsp. piperitum (mouth ulcers), Leopoldia comosa (toothache, headache), Micromeria graeca subsp. graeca (coughs) and Ceterach officinarum (malaria), while in the ethnoveterinary field, we have Pteridium aquilinum (wolf bites) and Spartium junceum (fractures of animal limbs).
Keywords: Abdominal Pain; Abdominal Pain: drug therapy; Anthelmintics; Anthelmintics: therapeutic use; Antiparasitic plants; Basilicata; Common Cold; Common Cold: drug therapy; Cough; Cough: drug therapy; Diuretics; Diuretics: chemistry; Diuretics: therapeutic use; Ethnobotany; Ethnopharmacology; Ethnopharmacology: methods; Furunculosis; Furunculosis: drug therapy; Geography; Humans; Italy; Lung Diseases; Lung Diseases: drug therapy; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plant Preparations; Plant Preparations: therapeutic use; Plants; Skin Diseases; Skin Diseases: drug therapy; Time Factors; Traditional; Veterinary plants; Wound Healing; Wound Healing: drug effects; Wounds and Injuries; Wounds and Injuries: drug therapy

The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G. (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
The following values have no corresponding Zotero field: accession-num: 15997399
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather

The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather

Exchange of atmospheric formic and acetic acids with trees and crop plants under controlled chamber and purified air conditions - Kesselmeier, J; Bode, K; Gerlach, C; Jork, E.-M (Atmospheric Environment, 1998)
We investigated the exchange of formic and acetic acids between the atmosphere and various tree species such as beech (Fagus sylvatica L.), ash (Fraxinus excelsior L.), spruce (Picea abies L.) Karst, holm oak (Quercus ilex L.), and birch (Betula pendula L.). and some crop-plant species such as corn (Zea mays, var. Banjo), pea (Pisum sativum, var. Solara), barley (Hordeum vulgare, var. Igri) and oat (Avena sativa, var. Wiesel). All experiments were done with dynamic enclosures ßushed with puriÞed oxidant-free air, containing only low or controlled amounts of the two acids. SigniÞcant and light-triggered emission of both acids from all tree species was observed. For one tree species (ash) a seasonal large increase in fall due to early leaf decomposition was found. The standard emission factors (30¡C and PAR"1000 kmol m2 s~1) given as (nmol m~2 min~1) for acetic and formic acids, respectively, were 8.1 and 29.7 (ash, autumn), 1.0 and 3.3 (ash, summer), 0.9 and 1.4 (beech), 0.7 and 1.45 (spruce), 1.9 and 2.4 (Holm oak) and 1.7 and 6.7 (birch). Rough estimation of global annual emissions range between 20 and 130 Gmol formic acid and 10 and 33 Gmol acetic acid. These numbers reßect a 15Ð30% contribution by forest emissions to the continental organic acid budget. As compared to the global total NMHC emissions low molecular weight organic acids are of minor importance. In contrast to the trees, none of the crop-plant species investigated showed an emission, but always a clear deposition of both acids. Both emission from trees as well as uptake by the agricultural plants could be related to transpiration rates and leaf conductances
Keywords: acetic acid; assimilation; Atmosphere; crop plants; exchange of volatile organic compounds; formic acid; leaf conductance; organic acids; Plants; Transpiration; Trees

Efeitos da poda radicular na produçáo de plantas de sobreiro em viveiro (quercus suber l.) - Santos, Maria de Lourdes; PAULINO, ISABEL MARGARIDA ORFÁO (II Congreso Forestal Español, 1997)
The work was accomplished in the Seed Laboratory of National Forestry Station. The aim is to observe, in the nursery plants production, the pruning root effects made at several levels. The seeds provenance are the selected trees. The results permitted to conclude that: • The plants submitted to a radicular pruning at 1/3 and 2/3 present a better thickening and become woody plants; • The plants submitted to a radicular pruning at 1/3 present higher size of aerial parts; • The plants submitted to a radicular pruning at 2/3 present higher rate of secondary roots. K.
Keywords: Nursery; Plants; Quercus suber; radicular pruning

Efeitos da poda radicular na produçáo de plantas de sobreiro em viveiro (quercus suber l.) - Santos, Maria de Lourdes; PAULINO, ISABEL MARGARIDA ORFÁO (II Congreso Forestal Español, 1997)
The work was accomplished in the Seed Laboratory of National Forestry Station. The aim is to observe, in the nursery plants production, the pruning root effects made at several levels. The seeds provenance are the selected trees. The results permitted to conclude that: • The plants submitted to a radicular pruning at 1/3 and 2/3 present a better thickening and become woody plants; • The plants submitted to a radicular pruning at 1/3 present higher size of aerial parts; • The plants submitted to a radicular pruning at 2/3 present higher rate of secondary roots. K.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Nursery; Plants; Quercus suber; radicular pruning

Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F. M.; Suarez, M. a; Pérez, A. (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)The following values have no corresponding Zotero field: accession-num: 9032619
Keywords: Data Collection; Humans; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plants; southern Spain; Spain; Structure-Activity Relationship; Traditional; Traditional phytotherapy

Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suárez, M A; Pérez, A (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)
Keywords: Data Collection; Humans; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plants; southern Spain; Spain; Structure-Activity Relationship; Traditional; Traditional phytotherapy

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Plant species as indicators of geochemical anomalies: Experiences onIlex aquifolium (holly) - Legittimo, P. Cellini; Ducceschi, L.; Martini, M. (Environmental Geology, 1995)
The distribution of Zn, Cd, Pb, and Cu, in plants growing in mineralized and sterile areas of Tuscany has been studied to verify if and to what extent metal- accumulating species represent evidence of geochemical anomalies in soils. Samples of leaves and twigs from trees were collected, and analyzed by means of differential pulse anodic stripping voltammetry (DPASV). Hollies, bram- bles, and Holm oaks in particular were considered in the mineralized area of Bottino, and the special aptitude of hollies in concentrating Cd with respect to the other metals has been verified. Cadmium has been previously recog- nized as a pathfinder for zinc ore bodies; the results of this investigation appear to point out the relevance of holly as a bioindicator of geochemical zinc anomalies. Lower metal concentration characterizes the same species from other mineralized and sterile zones, with the exception of the urbanized area of Florence, where relatively higher Zn concentrations in hollies appear to be due to atmospheric pollution.
Keywords: biogeochemical prospecting; Heavy metals; Plants

Plant species as indicators of geochemical anomalies: Experiences onIlex aquifolium (holly) - Legittimo, P Cellini; Ducceschi, L; Martini, M (Environmental Geology, 1995)
The distribution of Zn, Cd, Pb, and Cu, in plants growing in mineralized and sterile areas of Tuscany has been studied to verify if and to what extent metal- accumulating species represent evidence of geochemical anomalies in soils. Samples of leaves and twigs from trees were collected, and analyzed by means of differential pulse anodic stripping voltammetry (DPASV). Hollies, bram- bles, and Holm oaks in particular were considered in the mineralized area of Bottino, and the special aptitude of hollies in concentrating Cd with respect to the other metals has been verified. Cadmium has been previously recog- nized as a pathfinder for zinc ore bodies; the results of this investigation appear to point out the relevance of holly as a bioindicator of geochemical zinc anomalies. Lower metal concentration characterizes the same species from other mineralized and sterile zones, with the exception of the urbanized area of Florence, where relatively higher Zn concentrations in hollies appear to be due to atmospheric pollution.
Keywords: biogeochemical prospecting; Heavy metals; Plants